Private foundations tax law and compliance2017 cumulative supplement - Hopkins, Bruce R.; Blazek, Jody (John Wiley & Sons, Inc., 2017)
The must-have tax law reference for private foundations, updated for 2017 Private Foundations provides an authoritative reference and extensive analysis of tax law and compliance in the private foundations arena, with a wealth of practical tools to streamline applications, filing, and reporting. This 2017 Cumulative Supplement captures the latest regulatory developments for easy reference, with coverage of tax-exempt status, the self-dealing rules, mandatory distribution, jeaopardizing investments, taxable expnditures, annual reporting to the IRS, winding up a foundation's affairs, and much more. Comprehensive line-by-line instructions are included for a variety of exemption applications and tax forms, and easy-to-use checklists highlight areas of critical concern to help you avoid oversights. Sample documents are provided to guide the composition of organizational bylaws and various letters, and completed IRS forms provide practical reference for side-by-side comparison. With comprehensive, up-to-date coverage of the private foundations space alongside helpful tools and visual reference, this book is a resource every foundation's needs. Written by two of the nation's leading authorities on private foundations, this supplement provides essential guidance you can trust. Clear, concise instructions focused on real-world use makes this reference a critical companion for those tasked with the responsibility of maintaining a foundation's tax-exempt status and staying out of regulatory difficulties. Learn the latest guidelines for compliance, reporting, and eligibility Access the latest regulatory changes quickly and easily Organize reporting and applications with checklists and sample forms Find valuable tools and reference for all aspects of private foundation compliance Increasing IRS scrutiny makes compliance a more critical issue than ever before. An organization's tax-exempt status is generally vital to its continued operation, and a single oversight can put the future in jeopardy and staying out of regulatory difficulties. Private Foundations provides detailed instructions, examples, and much-needed answers on all aspects of private foundation tax law and compliance.
Includes bibliographical references and index. - CIP data; resource not viewed
Keywords: Nonprofit organizations -- Taxation -- Law and legislation -- United States; Charitable uses, trusts, and foundations -- Taxation -- United States; Fondations (Droit); Impôts; États-Unis; Charitable uses, trusts, and foundations; Taxation; Nonprofit organizations; Taxation; Law and legislation; United States